FUNGSI BADAN KEPEGAWAIAN DAERAH (BKD) DALAM PENGEMBANGAN PEGAWAI DI PROVINSI RIAU TAHUN 2016 - Triyana Ramadhani; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Government’s apparatus is one of the instruments in providing the maximum service for the public, which certainly should be provided with employees quality itself in terms an increase in human resources. Implemention of the Education and training of civil workers has been regulated in law No 5 year 2014 of the civil State Apparatus (ASN). But in practice has not been going well as still the presence of employees who does not have the skill, the placement of the ASN that is uneven, poor recruitment process or contains element of corruption, collusion, and nepotism (KKN). According to researcher who wants to find out the function of Agency’s Staffing area (BKD) in the development of employees in 2016The purpose of the researcher is to know the functions of BKD in the development of State Employees in Riau Province in 2016. This type of research is qualitative research method. The location of this research was located at the Agency’s Staffing Office area of Riau Province. The data collected by complementing the information through necessary interviews and requested documentation. While analysis of the data was performed using the method of qualitative analysis.Based on the results of the author’s research, draws the conclusion that inexecute Staffing Agency employees, development of the area of Riau Province announced three programs for human resources development of Riau Province area has announced three programs for human resources development apparatus including: The education and training (DIKLAT), government pre-position, and Promotion.Kata Kunci : Development, Fuction, BKD Riau Province